Carville : winning is everything, stupid [videorecording (DVD)] - Carville, James; Clinton, Bill, 1946-; Sharpton, Al; Matalin, Mary (Kino Lorber, 2025)
From masterminding Bill Clinton's 1992 presidential win to his insurgent role in the 2024 race, Democratic strategist James Carville has been one of the most influential forces in modern political history. The "Ragin' Cajun" looks back at his unlikely career and 30-year marriage to Republican consultant Mary Matalin. Featuring interviews with Bill Clinton, George Stephanopoulos and more.